Cameroon : 2021 Article IV Consultation and First Reviews Under the Extended Credit Facility and the Extended Fund Facility Arrangements and Requests for Waivers for Performance Criteria Applicability and Nonobservance and Modification Of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report, 2022)
Cameroon, the largest economy in the Central African Economic and Monetary Union (CEMAC), continues to face the repercussions of the COVID-19 pandemic. In July 2021, the IMF's Executive Board approved three-year arrangements under the Extended Credit Facility (ECF) and the Extended Fund Facility (EFF) for SDR 483 million (about USD 689.5 million, or 175 percent of Cameroon's quota) to support the country's economic and financial reform program. This followed two disbursements in 2020 under the Rapid Credit Facility (RCF) totaling SDR 276 million, equivalent to about USD 382 million or 100 percent of Cameroon's quota.